DAMPAK SUB SEKTOR BANK DAN LEMBAGA KEUANGAN NON BANK TERHADAP PERTUMBUHAN EKONOMI DI KOTA BITUNG - Mukuan, Danny (Sam Ratulangi University, 2017)
The regional development as implementation of wide, clear and responsible autonomy is giving big scope for the regional government to develop every sector of business in Bitung City.The result showed that contribution of sub-sector bank affect Bitung Economic Growt significantly based on = 0,01. And non bank financial institution doesn’t significantly affect the economic growth of Bitung city based on alpha level = 0,025.The result showed that sub-sector bank have positif relation while sub-sector non-bank institution have negative relation to economic growth of Bitung City with coefficient of correlation (R) 2,685 and coefficient of determination (R2) 0,721.F-test showed that Fcount Ftable with alpha = 0,01 (dF = 6). It means that H0 is rejected and the contribution of sub-sector bank and non-bank institution simultaneously affect the variable of economic growth with alpha = 0,01.